Strain variations in thrust belts. Insights from Talas Ala Tau (Kyrgyz Republic) - Pastor Galán, D.; Gutiérrez-Alonso, G.; Mulchrone, K. F.; Meere, P. A. (TRABAJOS DE GEOLOGÍA, 2010)
Computational strain analysis methods developed at University College of Cork have beenused to analyse several samples taken from Talas Ala Tau, Kyrgyzs Republic. These methods are moreaccurate and faster than manual methods. This study has revealed that the finite strain measured inTalas Ala Tau rocks (principally high quartz percentage feldespatic sandstones and feldespaticgraywackes) is independent of lithology and the general strain trend in this fold and thrust belt.